Carfilzomib or bortezomib with melphalan-prednisone for transplant-ineligible patients with newly diagnosed multiple myeloma - Facon, Thierry; Lee, Jae Hoon; Moreau, Philippe; Niesvizky, Ruben; Dimopoulos, Meletios; Hajek, Roman; Pour, Ludek; Jurczyszyn, Artur; Qiu, Lugui; Klippel, Zandra; Zahlten-Kumeli, Anita; Osman, Muhtarjan; et al. (Blood, 2019)
The phase 3 CLARION study compared carfilzomib-melphalan-prednisone (KMP) with bortezomib-melphalan-prednisone (VMP) in transplant-ineligible newly diagnosed multiple myeloma (NDMM) patients. Patients were randomized 1:1 to KMP or VMP for nine 42-day cycles (C). Patients received carfilzomib on days (D) 1, 2, 8, 9, 22, 23, 29, 30 (20 mg/m2: C1D1, C1D2; 36 mg/m2 thereafter) or bortezomib on D1, 4, 8, 11, 22, 25, 29, 32 (1.3 mg/m2; D4, 11, 25, 32 omitted for C5-9). Melphalan (9 mg/m2) and prednisone (60 mg/m2) were administered on D1-4. The primary endpoint was progression-free survival (PFS). Nine hundred fifty-five patients were randomized (intention-to-treat population: KMP, n = 478; VMP, n = 477). Median PFS was 22.3 months with KMP vs 22.1 months with VMP (hazard ratio [HR], 0.906; 95% confidence interval [CI], 0.746-1.101; P = .159). Median overall survival was similar and not reached in either group (HR, 1.08; 95% CI, 0.82-1.43). Overall response rate was 84.3% for KMP and 78.8% for VMP. Complete response rate was 25.9% for KMP and 23.1% for VMP. Minimal residual disease-negative rates were 15.7% (KMP) and 15.5% (VMP). Adverse events (AEs) of interest (any grade) occurring with a ≥5% higher patient incidence in the KMP arm were acute renal failure (13.9% [KMP] vs 6.2% [VMP]) and cardiac failure (10.8% vs 4.3%). Grade ≥3 AE rates were 74.7% (KMP) and 76.2% (VMP). Grade ≥2 peripheral neuropathy was lower for KMP vs VMP (2.5% vs 35.1%). Treatment with KMP in CLARION did not yield a statistically significant difference in PFS vs VMP. This trial was registered at www.clinicaltrials.gov as #NCT01818752.
Keywords: senioři; Oligopeptides; senioři nad 80 let; Multiple Myeloma; prednison; doba přežití bez progrese choroby; výsledek terapie; Bortezomib; Middle Aged; mužské pohlaví; oligopeptidy; Adult; Aged, 80 and over; Melphalan; mnohočetný myelom; ženské pohlaví; bortezomib; Humans; Prednisone; melfalan; Progression-Free Survival; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Aged; Treatment Outcome; lidé; Male